Parallel constrained global optimization for mathematical modeling of chemical reaction kinetics - Tikhonova, M.V.; Ryabov, V.V.; Spivak, S.I.; Gybaidullin, I.M. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
The application of constrained global optimization methods for solving inverse kinetic problems by reducing feasible domains is considered. The example of inhibited oxidation reaction for n-decane shows how the functional constraints can be used to take into account the correlation between physico-chemical values and the structural dependence between various reaction mechanisms. The parallel index method of constrained global optimization is used to solve the model identification problem. This method was previously successfully used for metal complex catalysis reactions in the unconstrained case.